Thermoeconomic analysis of an evaporative desiccant air conditioning system - Camargo, JR; Ebinuma, C. D.; Silveira, J. L. (Elsevier B.V., 2003)
In this paper, a thermoeconomic analysis method based on the first and second law of thermodynamics and applied to an evaporative cooling system coupled to an adsorption dehumidifier, is presented. The main objective is the use of a method called exergetic manufacturing cost (EMC) applied to a system that operates in three different conditions to minimize the operation costs. Basic parameters are the RIP ratio (reactivation air/process air) and the reactivation air temperature. Results of this work show that the minimum reactivation temperature and the minimum RIP ratio corresponds to the smaller EMC. This result can be corroborated through an energetic analysis. It is noted that this case is also the one corresponding to smaller energy loss. (C) 2003 Elsevier B.V. Ltd. All rights reserved.
Keywords: evaporative cooling; desiccant cooling; exergetic manufacturing cost